Integrating socio-cultural paradigms in nonprofit marketing-the case of blood donation among African communities in Australia - Polonsky, M.; Renzaho, A.; Brijnath, Bianca (Springer, 2010)
This paper examines how nonprofit marketers need to integrate socio-cultural factors when targeting minorities, using blood donation issues among African communities in Australia as an example. We start with an overview of the significance of African communities to Australia. Then blood donation patterns among migrant populations are discussed as well as the cultural beliefs about blood in the African continent and the intergenerational complexities that can arise between older and younger migrant donors. Marketing intervention models that seek to increase blood donation need to consider two factors: (1) geographical and generational cultural differences, that is, in relation to home and host country beliefs; and (2) intergenerational (young people vs. parents) differences in and attitudes to blood donation, especially when young people adopt the values of the host country faster than older migrants. Accounting for these cultural differences will enable non-profit and social services to develop culturally-competent marketing strategies to better meet the needs of different migrant communities. © 2010 Springer-Verlag.